2022
DOI: 10.1556/650.2022.32484
|View full text |Cite
|
Sign up to set email alerts
|

Ciszteamintartalmú szemcsepp alkalmazása cystinosisban

Abstract: A cystinosis ritka, aminosav-anyagcserét érintő, lizoszomális tárolási megbetegedés, melyben jellegzetes eltérés a cisztin felszaporodása és kikristályosodása a különböző szervekben, szövetekben, elsősorban a szemben és a vesében. Szemészeti vonatkozásban kiemelkedő jelentőségű a cisztinnek a corneában való lerakódása, ami nagyfokú fényérzékenység kialakulásához vezet. A kifejezett fényérzékenység jelentősen ron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Additionally, a randomized multicenter study has also indicated a decrease in crystal density, highlighting the improved efficacy of the viscous formulation compared to the 0.1% cysteamine-containing solution [21]. Some case reports have also reported significant therapeutic effects of Cystadrops ® in terms of decreasing photosensitivity and crystal density [5,22]. According to the clinical findings, it is plausible to hypothesize that the viscous formulation allows for prolonged retention of the active substance on the ocular surface, leading to elevated concentrations within the corneal layers, which, in turn, results in an enhanced dissolution of cystine crystals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a randomized multicenter study has also indicated a decrease in crystal density, highlighting the improved efficacy of the viscous formulation compared to the 0.1% cysteamine-containing solution [21]. Some case reports have also reported significant therapeutic effects of Cystadrops ® in terms of decreasing photosensitivity and crystal density [5,22]. According to the clinical findings, it is plausible to hypothesize that the viscous formulation allows for prolonged retention of the active substance on the ocular surface, leading to elevated concentrations within the corneal layers, which, in turn, results in an enhanced dissolution of cystine crystals.…”
Section: Discussionmentioning
confidence: 99%
“…The CYA content of the precorneal fluid, aqueous humor, and the corneal extract was analyzed by HPLC. The corneal retention (CR) of CYA, the apparent permeability (PappC) of CYA into the cornea, and the apparent permeability (PappAq) of CYA into the aqueous humor were calculated by using Equations ( 4), (5), and (6), respectively:…”
Section: Ex Vivo Penetration Testmentioning
confidence: 99%
See 1 more Smart Citation